Pendekatan Kualitatif Pada Persepsi Mahasiswa terhadap Kualitas Pendidikan Online - Bambang Subiyanto; Arthur Daniel Limantara; Elkana Lewi Santoso; Fauzie Nursandah; Sri Wiwoho Mudjanarko (CAHAYAtech, 2020)
The quality of online learning in institutions of higher education has become a growing concern in recent years. While some studies have focused on faculty and administrator perceptions, there is a lack of research conducted on students' perceptions of the quality of online education.This study uses qualitative methods to investigate students' perceptions from two universities and one community college regarding the quality of online education based on their own online learning experiences.Interviews and observations were conducted with three students. Various documents are collected, digitally, and printed. Positive and negative experiences of students are examined. Factors contributing to the experiences were also identified. The findings of this study reveal that flexibility, cost-effectiveness, availability of electronic research, easy connection to the Internet, and a well-designed classroom interface are positive experiences for students. Student negative experiences are caused by delayed feedback from the instructor, lack of technical support from the instructor, lack of self-regulation and self-motivation, a sense of isolation, monotonous teaching methods, and poorly designed course content. These findings can be used by instructors to understand students' perceptions about online learning, and ultimately improve their online learning practices.